PEMANFAATAN SARANA DAN PRASARANA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SD NEGERI 007 PULAU LAWAS: Penelitian Deskriptif - Rizki, Rizki Ananda; Fely, FELYANI YUSNISARI; Diana, Diana Prorida; Melda, Melda Deswita; Sinta, Sinta Rahmadani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the utilization of educational facilities and infrastructure in improving the quality of learning at SD Negeri 007 Pulau Lawas. This study uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews with 5 teachers, 1 principal, and 6 students, as well as direct observation of learning activities and utilization of school facilities. The results of the study indicate that the availability of facilities and infrastructure such as classrooms, libraries, teaching aids, and learning technology has had a positive impact on the teaching and learning process. However, obstacles such as limited maintenance, uneven distribution, and lack of teacher training in utilizing facilities are still challenges. This study concludes that optimizing the use of facilities and infrastructure, accompanied by increasing the capacity of educators, can further improve the effectiveness of learning. The recommendations from this study are to increase the maintenance budget, teacher training, and a more even distribution of facilities to support the quality of education in elementary schools.